A Rasch analysis of the community’s preference for different attributes of Islamic banks in Indonesia - Setiawan, Budi; Panduwangi, Morita; Sumintono, Bambang (Emerald, 2018)
Purpose: The purpose of this paper is to investigate the degree to which the different attributes of Islamic banks in Indonesia are preferred by the community. Design/methodology/approach: This paper uses a quantitative approach by applying Rasch analysis to measure the relative importance of 18 attributes of Islamic banks to the community. The data were collected by questionnaires, which were distributed online and completed by 345 respondents. In addition to the Rasch model, the preference of attributes was measured by a statistical inference test, using “SPSS” software, which employs binary logic regression related to the agreement between the performance of attributes and expectations. Findings: The instrument used in this study showed good reliability, and its validity fits the expected model. The results show that the assurance of financial security, friendliness and the application of Islamic principles in their operations are the most important attributes to be considered when people choose an Islamic bank. The degree of importance placed by the community on the various attributes of Islamic banks will have an effect upon the actual and perceived quality of those attributes. An increase in the community’s preference for a particular attribute will eventually be followed by an increased agreement between the actual performance of that attribute and the community’s expectation. Research limitations/implications: The varied profiles of individual respondents were not explored fully: this research relies solely on quantitative analysis. So, there is no empirical information to inform the Islamic banks as to which segments of the community should be the focus of their promotional activities. Originality/value: The use of Rasch analysis to measure the community’s preference for various attributes of Islamic banks has not been done previously.